Optimization Of Adolescent SelfIdentity Development: An Experimental Study - Afriyanti, Fajriyah Nur (Jurnal EduHealth, 2024)
Adolescent self-identity is indicated by self-awareness abilities that stem from organization, self-confidence, self-assessment, and self-observation. The process of forming this identity is viewed as an integration of personality integrity, personal change, social demands recognized by others, and future expectations. Therapeutic Group Therapy (TGT) provides a natural environment for adolescents due to the similarities and attractions within peer groups, thereby facilitating the formation of adolescent self-identity. This study aims to determine the effect of TGT on adolescent self-identity. The research design used is quasi-experimental, involving 78 adolescents as samples, consisting of 38 adolescents in the intervention group and 40 adolescents in the control group. The instruments used include a self-identity instrument and the TGT module. The intervention group received TGT for 7 sessions, each session lasting 30-45 minutes. Data analysis was performed using the dependent t-test. The results showed that the average self-identity score of adolescents was 7.00, with a range of 50-99. In the intervention group, the self-identity score before receiving TGT was 79.30 and increased to 83.32 after receiving TGT. Meanwhile, in the control group, the self-identity score before the intervention was 79.30 and slightly increased to 79.75 afterward. The difference in the average self-identity score was 9.339 with a p-value of 0.000 at a significance level of α = 0.05. The conclusion of this study is that TGT is effective in improving adolescent self-identity. Therefore, TGT can be used as a learning program in schools and at home, involving teachers, parents, and the community as an effort to enhance adolescent self-identity.